2011
DOI: 10.5194/nhess-11-1745-2011
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the performance of soil conditions and damage following an earthquake: a case study in Istanbul, Turkey

Abstract: Abstract. Istanbul city has experienced many strong earthquakes throughout its history and suffered extensive damage. The old Istanbul (Fatih and Eminonu districts), one of the most densely populated locations of Istanbul city, is a commercial centre and has many significant historical buildings. In this study, the data pertaining to the damage sustained by historical artifacts and structures from past earthquakes, are examined along with the soil amplification of the region, the liquefaction and slope stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…and 1885 C.E. The 1894 M w 7.3 earthquake (Ambraseys, 2002) affected a large area from Istanbul to Izmit (see isointensity curves from Eginitis, 1894, andin Ince, 2011). Ambraseys (2002) located the earthquake epicenter in the east of the Marmara Sea near the Hersek Peninsula.…”
Section: Inferred Rupture History For the çıNarcık Segment And Adjacementioning
confidence: 99%
“…and 1885 C.E. The 1894 M w 7.3 earthquake (Ambraseys, 2002) affected a large area from Istanbul to Izmit (see isointensity curves from Eginitis, 1894, andin Ince, 2011). Ambraseys (2002) located the earthquake epicenter in the east of the Marmara Sea near the Hersek Peninsula.…”
Section: Inferred Rupture History For the çıNarcık Segment And Adjacementioning
confidence: 99%
“…This has no impact on the level of damage as slope stability is not a high risk in the area. However, it was determined that soil amplification and partial liquefaction contributed to the destruction of historical artifacts and structures [8].…”
Section: Causes Of Seismic Failuresmentioning
confidence: 99%
“…In addition, some researchers of the incident are of the opinion that the quality of the superstructures was not the prime factor in determining the extent of damage and collapses: "...Our preliminary interpretation of the field data suggests that the type and width of structures do not significantly influence the degree of ground failure..." (Sancio et al, 2002). Ince (2011) researched the Old Istanbul (Turkey) city by using microzonation maps which are generated via geographical information system (GIS). Research has found that causes of the damage of the 1894 Istanbul earthquake to historical artefacts and structures were soil amplification and partial liquefaction.…”
Section: Introductionmentioning
confidence: 96%